A comparative study of gadolinium based oxide and oxyfluoride glasses as low energy radiation shielding materials. (May 2017) - Shamshad, L.; Rooh, G.; Limkitjaroenporn, P.; Srisittipokakun, N.; Chaiphaksa, W.; Kim, H.J.; Kaewkhao, J.
Abstract: The Gadolinium based oxide and oxyfluoride glass systems were prepared using conventional melt quenching method and studied for their radiation shielding properties. The mass attenuation coefficients (μm ), effective atomic numbers (Zeff ) and effective electron densities (Ne ) of the glasses at different photon energies were calculated theoretically by WinXcom program and experimentally determined by the transmission method. Moreover, the mass attenuation coefficient was investigated using Geant4 Monte Carlo code and compared with each other. The gamma ray energies were varied by Compton scattering technique. The values of attenuation parameters of both the glass systems have been found to be decrease with the increase in gamma ray photon energy. The results show that, the experimental values of mass attenuation coefficients, effective atomic numbers and effective electron densities are in good agreement with the theoretical values. It seems that Geant4 values are systematically lower than WinXCom. It could be caused by the simplification of geometry in Geant4. Although, the oxide glass system have superior shielding properties than oxyfluoride glass system, but, still, it has better shielding properties than commercial window glass and some existing concretes indicating the potential of this glass to be used as gamma ray shielding material. Moreover, there is no effect of fluoride component on the optical spectra. The optical absorption spectra of the glass systems under investigation have been shown with light transparency which is an edge to be used as radiation shielding material.